Color stability of resin cements exposed to aging - Ramos, N. C. [UNESP]; Luz, J. N. [UNESP]; Valera, M. C. [UNESP]; Melo, R. M. [UNESP]; Saavedra, G. S.F.A. [UNESP]; Bresciani, E. [UNESP] (Operative Dentistry, 2019)
The aim of this study was to evaluate the color stability of light-cured and dual-cured resin cements after artificial accelerated aging. Ten specimens (6-mm diameter and 2-mm thickness) for each of five resin cements were prepared: GC (dual-cured cement, GCem), Vb (light-cured cement, Variolink II only the base), Vbc (dual-cured cement, Variolink II base with catalyst), VV (light-cured cement, Variolink Veneer), and FR (flowable resin composite, light cured). The samples were polished and stored in an accelerated artificial aging machine for 308 hours (160 klx), with cycles of 120 minutes under light and 60 minutes in the dark. All aging was carried out in distilled water at 378C and light irradiation at 765 W/m2. The samples were evaluated in a spectrophotometer before and after aging, and results were calculated according to CIEDE2000. The data were statistically analyzed (one-way analysis of variance and Tukey test, 95% confidence). The results of DE00 were statistically significant for the type of cement (p,0.001), with differences among tested groups. Variolink II (base only and base + catalyst) and the flowable resin were the cements with the lowest color variations after the artificial accelerated aging. Considering the values DE00 of acceptability and perceptibility, none of the tested cements showed acceptable values.